Detection of Left Ventriculer Diastolic Dysfunction (LVDD) in Asymptomatic, Normotensive, ETT Negative Newly Detected Type-2 Diabetic Patients by Doppler Echocardiography - Banerjee, SK; Siddique, MA; Siddique, MA; Ahmed, CM; Jamil, AA; sarma, AK; Rahman, MA; Sultan, MA; Hauque, KMHSS (Nepalese Heart Journal, 2004)
Left ventricular diastolic dysfunction (LVDD) is the early manifestation of diabetic Cardiomyopathy, which is most often asymptomatic in early stage.